1994
DOI: 10.1002/ijc.2910580426
|View full text |Cite
|
Sign up to set email alerts
|

Hox gene expression in human small‐cell lung cancers xenografted into nude mice

Abstract: Transcription factors are crucial to an understanding of the molecular basis of neoplasia. Horneobox‐containing genes are a family of transcriptional regulators encoding DNA‐binding ho‐meodomains, involved in the control of normal development. Class‐1 human homeobox‐containing genes (HOX genes) display a peculiar chromosomal organization, perhaps directly related to their function. Aberrant expression of homeobox‐genes has been associated with both morphological abnormalities and oncogenesis. We have recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 19 publications
3
62
1
1
Order By: Relevance
“…In contrast, SCLC-75 and SCLC-6 displayed dramatically different HOX gene patterns of expression: in SCLC-75, all but HOXB7 genes were expressed, whereas SCLC-6 expressed only HOXB3. Although the general trends remained the same as those published previously [15], slight differences in the expression patterns were observed: SCLC-6 now expressed HOXB3 but not HOXB4, SCLC-10 and SCLC-82 expressed HOXB6, and SCLC-75 no longer expressed HOXB7. These differences might be explained by different sensitivities between RT-PCR and Northern blot- HpaII (methylation-sensitive), several band patterns were observed: a band of about 1 kb was seen in SCLC-6, SCLC-10 and SCLC-82, but not in SCLC-75 which exhibited bands at 4 and 5.5 kb; SCLC-10, and to a much lesser extent SCLC-82, also contained longer fragments indicating the presence of methylated restriction sites.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In contrast, SCLC-75 and SCLC-6 displayed dramatically different HOX gene patterns of expression: in SCLC-75, all but HOXB7 genes were expressed, whereas SCLC-6 expressed only HOXB3. Although the general trends remained the same as those published previously [15], slight differences in the expression patterns were observed: SCLC-6 now expressed HOXB3 but not HOXB4, SCLC-10 and SCLC-82 expressed HOXB6, and SCLC-75 no longer expressed HOXB7. These differences might be explained by different sensitivities between RT-PCR and Northern blot- HpaII (methylation-sensitive), several band patterns were observed: a band of about 1 kb was seen in SCLC-6, SCLC-10 and SCLC-82, but not in SCLC-75 which exhibited bands at 4 and 5.5 kb; SCLC-10, and to a much lesser extent SCLC-82, also contained longer fragments indicating the presence of methylated restriction sites.…”
Section: Resultssupporting
confidence: 80%
“…The main characteristics of the xenografted SCLC used in this study have been reported elsewhere [15]. Briefly, human SCLC tissues, obtained through fibroscopy or surgical excision of tumors from patients with histologically confirmed diagnoses of SCLC, were xenografted into 6-8-week-old Swiss/athymic mice (IFFA-Credo, Lyon, France) by s.c. implantation.…”
Section: Tumorsmentioning
confidence: 99%
See 3 more Smart Citations